2006
DOI: 10.1007/bf03325913
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trace metals on halophilic and mixed cultures in anaerobic treatment

Abstract: ABSTRACT:Trace metals are known to stimulate the activity of anaerobic methanogenic bacteria involved in the degradation of organic matter. The objective of this research was to investigate the effect of three trace metals, iron, nickel and cobalt on the activity of halophilic methanogens, digester sludge and a mixed culture of halophilic bacteria and digester sludge, at various salt concentrations. Iron slightly stimulated both initial and maximum specific methanogenic activity (SMA) of halophilic methanogens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 7 publications
(9 reference statements)
1
9
0
Order By: Relevance
“…Moreover, a stimulation of the activity and population of halophilic methanogens was also reported after adding Ni 2+ and Co 2+ during the anaerobic degradation of organic matter at different salt concentrations. [39] In the same way, it was reported that the methanogenic activity of Methanosarcina sp. increased considerably after the addition of trace nutrients (Ni 2+ and Co 2+ ) in sulphide-containing media during the anaerobic treatment of wastewaters containing methanol.…”
Section: Identification Of the Microorganisms Involved By Molecular Bmentioning
confidence: 74%
“…Moreover, a stimulation of the activity and population of halophilic methanogens was also reported after adding Ni 2+ and Co 2+ during the anaerobic degradation of organic matter at different salt concentrations. [39] In the same way, it was reported that the methanogenic activity of Methanosarcina sp. increased considerably after the addition of trace nutrients (Ni 2+ and Co 2+ ) in sulphide-containing media during the anaerobic treatment of wastewaters containing methanol.…”
Section: Identification Of the Microorganisms Involved By Molecular Bmentioning
confidence: 74%
“…The observed differences in biogas yield and digestibility of microalgal biomass grown at different IONPs concentration clearly signify the active role of IONPs in improving the digestion of microalgal biomass. As discussed above, the improvement in the biogas production with increasing the IONPs concentration could be attributed to the fact that the iron nanoparticles act as a catalyst for simulating the activity of anaerobic microflora 41 , 42 . Overall, 25.14% enhancement in biogas production was observed with an increase in IONPs dose to 30 mg L −1 as compared to control.…”
Section: Resultsmentioning
confidence: 99%
“…The solution is highly recommended because of environmental benefits such as potentially lower air pollution by H 2 S/SO 2 emission and lesser impact on human health. Krongthamchat et al 83 reported that the addition of iron as a trace metal could reduce the lag time of a mixed culture. Liu et al 75 stated that iron ions released from the dissolution of magnetic NPs can stimulate bacterial activities.…”
Section: Addition Of Fementioning
confidence: 99%